Morphological and Molecular Characteristics of Sarcocystis aucheniae Isolated from Meat of Guanaco (Lama guanicoe) - Regensburger, Cristian Daniel (2015)
Background: Sarcocystosis in South American camelids (SAC) is an important parasitic disease which results in economical loss due to carcass condemnation. Meat products from camelids are significant source of animal protein in several American countries. Sarcocystis spp. producing macroscopical cysts in these animals have been nominated as S. aucheniae, S. tilopodi, and S. guanicoecanis. The aim of the present study was to characterize morphologically and molecularly Sarcocystis spp. producing macroscopical cysts in guanacos (Lama guanicoe). Methods: Samples of macroscopical cysts were dissected from guanaco muscles slaughtered in Santa Cruz province, Argentina. The samples were processed by transmission electron microscopy, polymerase chain reaction (PCR), cloning and sequencing studies. Results: Cyst wall villar protrusions were irregular with a “tree” or “cauliflower-like” shape which measured 3-4.5 µm height by 2.5-3.5 µm width. A consensus 18S rRNA full gene sequence of 1875 bp was obtained and showed the highest identity (≥ 99 %) with sequences of S. aucheniae reported in GenBank. The ultra structure of the cyst wall from macroscopical cysts and 18S rRNA gene obtained from guanacos were identical and consistent with the descriptions of S. aucheniae. Conclusion: This study confirms that guanacos are infected by the same Sarcocystis spp. affecting other SAC, named S. aucheniae, and reinforce the suggestion that nomination of new species should contain morphological and molecular data to reach validity. In future, this data could be useful to obtain proper identifications in post-mortem inspection and helpful to improve meat safety.